A study for studio design layout and auxiliary facility for Department of Architecture in UiTM Seri Iskandar Campus / Ahmad Farid Ab Latif and Amirul Amin Ismail - Ab Latif, Ahmad Farid; Ismail, Amirul Amin (2018)
Studio is an essential working place for architecture students to express their work in relation to how they experience and communicate themselves within their atmosphere. As an architecture student, working in the studio will help us to boost our performance efficiently. Universiti Teknologi MARA (UiTM) has been regarded as one of the oldest and pioneering architecture and built environment school in Malaysia and essentially has worldwide recognition. However, due to the high intake volume of students, it might lead to improper studio layout and subsequently some of the impromptu studio arrangement will definitely affect students’ performance. This initiative was specifically aimed to identify the preferred criteria of studio design based on the collective survey and data from the students’ perspective. The essence of time must be contemplated in order to achieve effectiveness of studio usage. Several methods that were used to gather data mainly through interview with students, observation and questionnaire. Auxiliary facilities provided in the studio are considered supporting facilities. Results reveal that the most effective studio layout is linear organization and this is proven to be the most desired by end-users.